Physical properties of guanidinium trifluoromethanesulfonate-methyldiethanolamine aqueous mixtures and their CO2 absorption capacities / Nor Asrina Sairi - Nor Asrina, Sairi (2011)
In this work, the physical properties i.e. density, viscosity and CO2 solubility studies were conducted on the aqueous systems of N-methyldiethanolamine (MDEA) and guanidinium trifluoromethanesulfonate [gua][OTf]. The studies were carried out at various concentration of MDEA (1 – 4 M) and [gua][OTf] (0.1 – 2 M). The temperature and pressure were also varied depending on the study involved.